Knowledge and attitude on umbilical cord blood stem cell therapy among bachelor nursing students in Lalitpur Metropolitan City - Bajracharya, Karuna; Singh, Shreejana; Joshi, Deepak Raj; Lawot, Isabel (Journal of Karnali Academy of Health Sciences, 2024)
Background: Stem cells are immature cells that have the ability to mature into different types of functioning cells as needed by the body. Umbilical cord blood is one of the richest sources of stem cells. It is vital for nurses to keep up-to-date with current advances in stem cell science and nurses can play a crucial role in providing first-hand information to the public about stem cells and umbilical cord blood banking. Therefore, this study is aimed to identify the knowledge and attitude regarding umbilical cord blood stem cell therapy among bachelor nursing students. Method: A descriptive cross-sectional research design was used to assess the knowledge and attitude of 263 nurses studying bachelor in nursing science and post-basic bachelor in nursing in different selected nursing colleges of Lalitpur metropolitan city. Multi-stage cluster sampling was used to select respondents. Data was collected using a self-developed self administered Google form questionnaire. Knowledge level was classified as good, moderate and poor, and attitude as favourable, neutral and unfavourable. Descriptive and inferential statistical methods were used to analyze data. Results: Nearly half of the nurses had poor knowledge (49.4%) and the only 6.8% nurses had good knowledge. However, the majority of nurses (93.9%) had a favorable attitude regarding umbilical cord blood stem cell therapy. There is no association between knowledge level and attitude (p=0.224). Conclusion: Nurses had poor knowledge and favorable attitudes regarding umbilical cord blood stem cell therapy. Nurses have the potential to play a vital role in providing information to the general population regarding stem cell therapy, therefore, it is most important to include these areas in the nursing curriculum.